Spatial geometry in ENEM: a proposal for a study through the theory of significant learning (Research, Society and Development, 2022)
The main objective of this research was to discuss the study of Prisms through the questions of the National High School Exam - Enem, adopted in Brazil, based on David Ausubel's Theory of Meaningful Learning. Ausubel. The study included 03 students from the 3rd year of high school living in the city of Cajazeiras, Paraíba, northeastern Brazil. We apply a qualitative methodology of the case study type. The results sought that the students, for the most part, were able to understand what a prism is, how to calculate its volume and its total area, given their good performance on the issues related to the content. In addition, we noticed the relationship that the questions chosen for this study have with other mathematical content, as well as with everyday activities. Therefore, we emphasize the importance of working on Primes content so that students feel motivated to study it and realize its use in their daily lives.